Analysis of heterogeneity of the different health technology assessment reports produced on the transcatheter aortic valve implantation in patients with severe aortic valve stenosis at low surgical risk - Rumi, Filippo; Fortunato, Agostino; Antonini, Debora; Siviero, Ludovica; Cicchetti, Americo (Frontiers in Cardiovascular Medicine, 2023)
Symptomatic severe aortic stenosis is a congenital or acquired aortic valve disease, that occurs when heart's aortic valve narrows. It represents the most common valvular disease in adults and generally has a degenerative nature. Transcatheter aortic valve implantation, because of its non-invasive approach, has become the standard treatment in patients who are ineligible to surgery or at high surgical risk and is increasingly being performed in patients at intermediate to low surgical risk. The aim is to analyse the heterogeneity and explore the limitations of current Health Technology Assessments on TAVI.For the purpose of this analysis a review of the literature based on manual research were performed. A PICO model was used to gather HTA reports assessing TAVI in the treatment of patients affected by symptomatic severe aortic valve stenosis at low surgical risk. Furthermore, a manual search has been developed to also include assessments from the Haute Autorité de Santé.At the end of the investigation, it has emerged a certain degree of heterogeneity in the evidence factored and in the recommendations on the Technology. Relatively to the clinical domains, the main drivers for the disparity are found in the type of evidence considered and about the use or not of the GRADE methodology to evaluate the quality of the clinical evidence included. Another element concerns the chosen device generation assessed within the evaluation. In order to perform the economic evaluation a cost utility analysis and a budget impact model were developed. Despite some elements of heterogeneity, the economic assessments demonstrate a favourable or dominant cost-effectiveness profile for TAVI compared to SAVR.Despite the presence of heterogeneity elements both in clinical and economic domains, HTA agencies reached the same recommendations on the use of TAVI. It emerged the need for a centralized vision on the 'strong' domains, giving up freedom to local bodies to adapt to their context the 'soft' ones. This approach could have the potential to strengthen the role of HTA in Europe by ensuring faster decision-making and equity of access to health innovations, and reduce the heterogeneity in the assessment methods.